2011
DOI: 10.1007/s00792-011-0406-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structural basis for thermal stability between archaeal and bacterial proteins

Abstract: In this study, the structural basis for thermal stability in archaeal and bacterial proteins was investigated. There were many common factors that confer resistance to high temperature in both archaeal and bacterial proteins. These factors include increases in the Lys content, the bends and blanks of secondary structure, the Glu content of salt bridge; decreases in the number of main-side chain hydrogen bond and exposed surface area, and changes in the bends and blanks of amino acids. Certainly, the utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…8b) gave insight into some of the factors that may confer stability in the Mj enzyme. The amino acid substitutions and their locations in Mj are consistent with thermostabilization strategies adopted by hyperthermophilic enzymes [34, 3739]. Thermostable enzymes typically have more ion pairs (salt bridges), especially in networks, more hydrophobic interactions in their interior, and a larger number of bulkier hydrophobic side chains as compared to their mesophilic counterparts.…”
Section: Discussionmentioning
confidence: 60%
“…8b) gave insight into some of the factors that may confer stability in the Mj enzyme. The amino acid substitutions and their locations in Mj are consistent with thermostabilization strategies adopted by hyperthermophilic enzymes [34, 3739]. Thermostable enzymes typically have more ion pairs (salt bridges), especially in networks, more hydrophobic interactions in their interior, and a larger number of bulkier hydrophobic side chains as compared to their mesophilic counterparts.…”
Section: Discussionmentioning
confidence: 60%
“…A comparison of structural basis for thermal stability in archaeal and bacterial proteins revealed that increased salt bridge and Glu content are among the important stabilizing factors of heat-resistant bacterial proteins [81]. Most thermophilic proteins tend to have more salt bridges, and achieve higher thermostability by up-shifting and broadening their protein stability curves.…”
Section: Resultsmentioning
confidence: 99%
“…The Halanaerobiales follow an experimentally confirmed salt-in strategy without an acidic proteome. Instead, they hydrolyze Glutamine (Q) and Asparagine (N) to compensate for the lack of acidic amino acids ( Bardavid and Oren 2012 ). However, the genome of Acethalobium arabaticum , a member of the Halanaerobiales , encodes a more acidic proteome, similar to Salinibacter and Salinicoccus ( supplementary fig.…”
Section: Discussionmentioning
confidence: 99%